Analyzing E-banking in Iran and other Countries - Abbasi, Ebrahim; Ranjbar, Hojat; Ranjbar, Saeed; Shabanpour, Marzie; Alipour, Sara (Pure and Applied Science Advances, 2014)
E-banking is the most recent outcome of modern banking services which provides unlimited markets and paves the way for better risk management.it has made a big progress during recent years especially in developed countries. However, new comer with innovative idea and strategy definitely can make position in this sector. The evolution consideration and current circumstances of E-Banking can help analyzing issues like: existing e-banks and entrants to boost the economic growth.